A silicon strip detector dose magnifying glass for IMRT dosimetry - Wong, J.H.D.; Carolan, M.; Lerch, M.L.F.; Petasecca, M.; Khanna, S.; Perevertaylo, V.L.; Metcalfe, P.; Rosenfeld, A.B. (The American Association of Physicists in Medicine, 2010)
Methods: A full characterization of the detector was performed, including dose per pulse effect, percent depth dose comparison with Farmer ion chamber measurements, stem effect, dose linearity, uniformity, energy response, angular response, and penumbra measurements. They also present the application of the CMRP DMG in the dosimetric verification of a clinical IMRT plan. Results: The detector response changed by 23% for a 390-fold change in the dose per pulse. A correction function is derived to correct for this effect. The strip detector depth dose curve agrees with the Farmer ion chamber within 0.8%. The stem effect was negligible (0.2%). The dose linearity was excellent for the dose range of 3-300 cGy. A uniformity correction method is described to correct for variations in the individual detector pixel responses. The detector showed an over-response relative to tissue dose at lower photon energies with the maximum dose response at 75 kVp nominal photon energy. Penumbra studies using a Varian Clinac 21EX at 1.5 and 10.0 cm depths were measured to be 2.77 and 3.94 mm for the secondary collimators, 3.52 and 5.60 mm for the multileaf collimator rounded leaf ends, respectively. Point doses measured with the strip detector were compared to doses measured with EBT film and doses predicted by the Philips Pinnacle treatment planning system. The differences were 1.1%+/- 1.8% and 1.0%+/- 1.6%, respectively. They demonstrated the high temporal resolution capability of the detector readout system, which will allow one to investigate the temporal dose pattern of IMRT and volumetric modulated arc therapy (VMAT) deliveries. Conclusions: The CMRP silicon strip detector dose magnifying glass interfaced to a TERA ASIC DAQ system has high spatial and temporal resolution. It is a novel and valuable tool for QA in IMRT dose delivery and for VMAT dose delivery.